Virtual Inhibition Analysis of Bioactive Compound Brazilin (Caesalpinia sappan L.) Toward Progesterone Receptor or Lonaprisan in Breast Cancer Proliferation - Ayu Puspitaning Dewi Harnis; Nur A.H.M. Hasan; Yuni K. Janah; Chaidila A. Tsamara; Fatchiyah Fatchiyah (Biotropika: Journal of Tropical Biology, 2020)
Breast cancer is one of the leading causes of death worldwide. The pathway of breast cancer in KEGG shows that the most effective pathway is through the progesterone receptor (PR). Brazilin is a bioactive compound of secang (Caesalpinia sappan L.) used to inhibit breast cancer through survivin and Bcl-2 pathway but the interaction with PR route is unknown. This research was conducted to determine the virtual interaction between brazilin and PR and its comparison with lonaprisan, so the potential of breast cancer drugs that can overcome through three targets at once with minimal side effects is expected to be known. There are five docking interactions, including the interaction of PR-progesterone, PR-brazilin, PR-brazilin-progesterone, PR-lonaprisan, and PR-lonaprisan-progesterone. Protein and ligand preparation was performed by using Discovery Studio Client 2019 and PyRx 0.8, molecular docking was performed by using Hex 8.0.0 and visualization used Discovery Studio Client 2019. Virtual interaction results shows that lonaprisan has the most stable bond (lowest binding energy), -333.8kJ/mol but when progesterone was docked afterwards the result shows the opposite. Brazilin has a more stable bond compared to lonaprisan with a difference of 2.1kJ/mol and supported by hydrophobic bonds also capable of changing the position of progesterone in binding to PR so that it is estimated that brazilin has the potential as SPRMs, an alternative breast cancer drug to replace lonaprisan. Herbal medicine with brazilin can be estimated to fight breast cancer through 3 targets at once (survivin, Bcl-2, PR).